Annual Report on Exchange Arrangements and Exchange Restrictions 1952. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1952)
This paper recognizes the difficulties and problems being faced by member countries under present circumstances and the uncertainties resulting from the strained international situation and rearmament. After the various relaxations and intensifications, there still remains a widespread use of restrictive practices by the IMF's members. Despite some similarity between the restrictive systems of different countries, there is, as noted, a widespread diversity in the practices of IMF members. Multiple currency practices of many types and a variety of other devices are employed either in isolation or in combination. The purpose of many of the restrictions employed is to cope with balance of payments difficulties of the country imposing them. Some of the difficulties, however, are the result of measures in important export markets. Limitations on imports by one country, through exchange or trade restrictions or other devices, restrict the earnings of other countries and consequently may result in the latter restricting their payments.